INTERRELIGIOUS DIALOGUE AS THE FOUNDATION OF RELIGIOUS ANTI-VIOLENCE: Praxis Implications of the Dialogality of Armada Riyanto and Pope Francis - Egidius Egiagu (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2024)
The focus of this research aims to explore the views of Armada Riyanto and Pope Francis on anti-violence dialogue, especially in the context of prevention and reconciliation. This research will go through an analysis of the practical approach of these two personages in implementing dialogue as a preventive and reconciliatory tool in facing violence in the name of religion. The point of emphasis is not only to reject the emergence of violence in the name of religion, but also to encourage proactive preventive efforts. Armada Riyanto and Pope Francis believe that dialogue can be an effective means to deal with the potential for violence and to respond to the reality of existing violence. The views of these two personages emphasize the importance of dialogue as a powerful preventive instrument. Through dialogue, people can understand each other, reduce tensions, and find solutions that are fair to all parties. Both are aware that one cannot ignore the reality that life adepting a religion often displays the face of violence. A dialogal spirit becomes the foundation of prevention and reconciliation in dealing with the reality of conflict, without having to lead to violence. It is hoped that the results of this research can provide new insights into the importance of dialogue in building communities of religious believers who are more peaceful and tolerant.